Characterization of ANFO explosive by high accuracy ESI(±)–FTMS with forensic identification on real samples by EASI(−)–MS. (April 2015) - Hernandes, Vinicius Veri; Franco, Marcos Fernado; Santos, Jandyson Machado; Melendez-Perez, Jose J.; Morais, Damila Rodrigues de; Rocha, Werickson Fortunato de Carvalho; Borges, Rodrigo; de Souza, Wanderley; Zacca, Jorge Jardim; Logrado, Lucio Paulo Lima; Eberlin, Marcos Nogueira; Correa, Deleon Nascimento
Highlights: Ammonium nitrate fuel oil (ANFO) is one of the most widely used explosives in the world. In Brazil, ANFO stolen from quarries has been widely applied in ATM explosions by criminals. For forensic purposes, pre-blasts and post-blasts ANFO were identified by mass spectrometry, MS. An important MS negative ion marker ( m / z 210), for both pre and post-blasts ANFO, is reported here. Ambient MS, here EASI–MS, is a powerful tool to study chemicals in forensic surface samples. Abstract: Ammonium nitrate fuel oil (ANFO) is an explosive used in many civil applications. In Brazil, ANFO has unfortunately also been used in criminal attacks, mainly in automated teller machine (ATM) explosions. In this paper, we describe a detailed characterization of the ANFO composition and its two main constituents (diesel and a nitrate explosive) using high resolution and accuracy mass spectrometry performed on an FT-ICR-mass spectrometer with electrospray ionization (ESI(±)–FTMS) in both the positive and negative ion modes. Via ESI(−)–MS, an ion marker for ANFO was characterized. Using a direct and simple ambient desorption/ionization technique, i.e., easy ambient sonic-spray ionization mass spectrometry (EASI–MS), in a simpler, lower accuracy but robust single quadrupole mass spectrometer, the ANFO ion marker was directly detected from the surface of banknotes collected from ATM explosion theft.